RETRACTED: CircSETD3 (Hsa_circ_0000567) Suppresses Hepatoblastoma Pathogenesis via Targeting the miR-423-3p/Bcl-2-Interacting Mediator of Cell Death Axis - Li, Xin; Wang, Haojie; Liu, Zhijie; Abudureyimu, Alimujiang (Frontiers in Genetics, 2021)
Background: Up until now, the role of circSETD3 (Has_circ_0000567) in regulating cancer development has been reported in several tumors, but the role and regulatory mechanism of circSETD3 in hepatoblastoma (HB) remain unclear. Methods: The qPCR and western blotting were used to determine the mRNA and protein levels in the present study. Stability of circular RNA was detected by RNA digested experiments. The gain-of-function and rescue experiments were used to explore the function and mechanism of circSETD3 in HB. Cell counting kit-8, colony formation, transwell assay, and xenograft mice model were used to detect effects and regulatory mechanism of circSETD3/ miR-423-3p/Bim axis on cell aggressive phenotype in vitro and in vivo. Results: Here, we identified that circSETD3 downregulated in both HB clinical tissues and cell lines, compared to that of normal tissues and cells. Further gain-of-function experiments validated that circSETD3 overexpression inhibited cell proliferation, viability, migration, epithelial-mesenchymal transition (EMT) and tumorigenesis, and induced cell apoptosis in HB cells. Next, we validated that miR-423-3p targeted both circSETD3 and 3’ untranslated region (3’UTR) of Bim, and circSETD3 positively regulated Bim in HB cells through sponging miR-423-3p in a competing endogenous RNA (ceRNA)-dependent manner. Furthermore, through conducting reversal experiments, we evidenced that the inhibiting effects of circSETD3 overexpression on HB development were abrogated by upregulating miR-423-3p and downregulating Bim. Conclusion: Taken together, we evidenced that circSETD3 sponged miR-423-3p to upregulate Bim, resulting in the inhibition of HB development.